Texto e contexto das leis orgânicas dos ensinos industrial, comercial e agrícola: 1942-1946 - Ferreira, Solange Carneiro Molinaro (1980)
This study intends to characterize and delineate the content of Or'ganic Laws of Industrial Education (DecreeLaw No. 4073,1942), of Commercial Education(Decree-Law No. 6141, 1943), and of Agricultural Education (Decree-Law No. 9613, 1946) and the linkages with the political, social, economic, administrative, and educational contexto This study LS organized in four chapters. The first and second chapters utilize the historical method. Chapter I focuses on the evolution of the occupational education in Brazil. Chapter 11 deals with aspects of the aforementioned context which influenced the context of the organic laws. The last two chapters have the purpose of speculating upon the ideology contained in the text of the organic laws. Chapter 111 presents the analysis of the text, while Chapter IV analyzes and interprets which link the content of those laws to ideological prernises the political, social, economic, administrative, and educational contexto This study indicates that the texts of Organic Lmvs 'of Industrial, Commercial, and Agricultural Education, created by the government reflect their ideological functions. The purpose of these functions was to attain to the goals of the 'Estado Novo' through the consolidation of the social order and through mechanisms of social maintenance and social reproduction. This study also indicates the textual analysis of Organic Laws did not fulfill needs of the national process of industrialization. addition, the laws did not rnect the need to construct model Df an educational system which could satisfy that the In a the requirements of the productive system as well as the social developrnent dernanded by the political, social, econornic, administrative, and educational contexto